URGENSI PENATAAN REGULASI DAS PRIORITAS DALAM RANGKA TERTIB HUKUM ADMINISTRASI DAS TERPADU DI INDONESIA - I Gusti Ayu Ketut Rachmi Handayani (Faculty of Law, Universitas Diponegoro, 2013)
Abstract Destruction of Ciliwung watershed is one of the causes that make Jakarta will not be free from floods. Ciliwung watershed destruction also triggered the destruction of the water catchment area around the peak. Has led to the destruction of Ciliwung river discharge rapidly changing. Integrated watershed management is resource management efforts involving various parties who participate from the planning stages through to monitoring and evaluation. Classification is based on the Government Regulation No. 37 in 2012 that 8 (eight) watershed in the watershed JABODETABEK, Angke-Pesanggrahan, DAS of Krukut, DAS of Ciliwung, DAS of Buaran, DAS of Sunter, DAS of Cakung, and DAS of Cisadane and DAS of Bekasi, a restored watershed carrying capacity and categorized as Priority One. Optimization of central and local governments in order structuring regulation is needed in order to administration of law of integrated watershed management. Keywords: Regulation, Integrated Watershed, Administrative Law Abstrak Rusaknya DAS Ciliwung adalah salah satu penyebab yang membuat Jakarta tidak akan terbebas dari Banjir. Rusaknya DAS Ciliwung juga memicu rusaknya daerah tangkapan air di sekitar Puncak. Rusaknya DAS Ciliwung telah menyebabkan debit sungai cepat berubah. Pengelolaan DAS terpadu merupakan upaya pengelolaan sumber daya yang menyangkut berbagai pihak yang berperan sejak tahapan perencanaan hingga monitoring dan evaluasinya. Berdasarkan Klasifikasi PP No. 37 Tahun 2012 bahwa 8 (delapan) DAS di JABODETABEK yaitu DAS Angke-Pesanggrahan, DAS Krukut, DAS Ciliwung, DAS Buaran, DAS Sunter, DAS Cakung, DAS Cisadane dan DAS Bekasi, merupakan DAS yang dipulihkan daya dukungnya dan masuk kategori Prioritas Satu. Optimalisasi pemerintah pusat dan daerah dalam rangka penataan regulasi sangat diperlukan dalam rangka tertib hukum administrasi pengelolaan DAS terpadu. Kata Kunci: Regulasi, DAS Terpadu, Hukum Administrasi Negara